Imunodetecção em frações protéicas de cérebro de abelha Apis mellifera de proteínas associadas a vesículas sinápticas, miosina-V e CA2+/ calmodulina quinase II (CaMKII) - Moraes, Viviane Rodrigues Alves de (2005)
Neurotransmitter secretion and subsequent release, shares many features with constitutive membrane trafficking. Intracellular membrane fusion in eukaryotic cells involves a several family’s proteins, including SNARES, Rabs, Sec1/Munc-18 (SMproteins), and molecular motors in an evolutionary conserved machinery. Honeybee brain has been successfully used as a neurobiology model to investigate memory, learning and behavior. In the current work, through the techniques Western blot and immunohistochemistry, SNAREs proteins, myosin-V, and, CaMKII are identified in protein fractions and tissue of honeybee worker’s brain (Apis mellifera). By immunoblotting, using specific antibodies: syntaxin and CaMKII was probed in the casts drone and queen; for the brain fractions H and S1 of worker bee, rabbit and rat, the CaMKII antibody was tested; the brain fractions H, S1, P1, S2, P2, and enriched membrane fraction P2TX, of worker bee, chicken, rabbit and rat was probed with antibody against myosin-Vfor comparison betweenyours respective immunoreactivity. In addition, honeybee worker’s brain regions fractions were tested with antibodies Clathrin and CaMKII. Indeed, the immunoreactivity for the antibodies raised against vertebrates, showed conserved regions in hymenoptera. This orthology suggests that many of the proteins important for transmitter release have homologs involved in intracellular vesicle transport, and all forms of vesicle trafficking share common basic principles with others organisms.